Development of a Facial Recognition-based Attendance System using Binary Patterns Histograms Method and Telegram Bot Notification - Qois Amin Fauzan; Aris Budianto; Cucuk Wawan Budiyanto (Journal of Informatics and Vocational Education, 2022)
In carrying out attendance activities, most schools still use the manual attendance method, which utilizes the attendance book as a medium. However, the presence of the manual still causes some problems that arise when using this method. With the aim of this study, a "Facial Recognition-Based Attendance System" was created. This study used the Local Binary Pattern Histogram (LBPH) method to detect and recognize faces. The system is made to recognize the student's face and name, which the attendance system will then carry out along with the student's identity in the form of Name and Absence Number in real time to find out that the student is present in the class. The names that have been diabase can be saved through the XLS format. The result of this study is a facial recognition-based attendance system using the LBPH (Local Binary Pattern Histogram) method. The system is web-based, so users can easily access it through the internet. This research method uses research and development methods. This research stage consists of research and information collection, planning, and product draft development. The results of this study showed the feasibility level of facial recognition-based attendance systems. The eligibility rate obtained showed a score of 78.98%. From these results, this system is worthy of being used as an attendance system.